“Iraqi Freedom”: Counterhegemonic Narrations of the Occupation of Iraq from Blogs to Books (Altre Modernità, 2011)
The terrorist attacks of 9/11 made people look at the Web as a source of news and live accounts in an unprecedented way. It was during the subsequent  war on Iraq, however, when most professional journalists were embedded, that the internet finally became an established source of news in terms of news websites and, especially, of a new media merging journalism and life-narrative: blogs.  Several ‘warblogs’ were written by Iraqis in English, providing a view of the war and occupation “from within”, as well as a less prejudiced representation of Iraqis in particular and Muslim communities in general. Some of these ‘authentic’ voices were later absorbed into the mainstream when their war accounts were turned into books and packaged for new audiences. This paper focuses on two female blogs from Iraq, Baghdad Burning by Riverbend and IraqiGirl by HNK, discussing the way new media allow these women to articulate their voices and convey their identities in a way that also challenges dominant narrations of the war and occupation, as well as of Muslim women as passive and victims. While their blog narratives challenge the stereotypical notion of the Arab woman and a specific ‘exoticist’ imaginary, however, in becoming books their blogs are inevitably absorbed into hegemonic representations of Arab women as a consequence of the marketing practices surrounding the book as a consumer good, which are paradoxically promoted by Western ‘liberals’ trying to disseminate a specific counterhegemonic discourse of the war.